2013
DOI: 10.11622/smedj.2013033
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical safe zone for medial opening oblique wedge high tibial osteotomy

Abstract: This study was carried out to determine the thickness of the ASZ, including its relationship to the fibular tip, and the level of PCL insertion at the proximal tibia. METHODS Ten pairs of embalmed, normal cadaveric legs containing intactPTFJs were included in the study (age 48-60 years). All specimens were disarticulated at the level of the knee joint. Soft tissues around the proximal tibia and PTFJ were dissected to identify the articular cartilage of the tibial condyles and PCL insertion.The posterior capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In the standard AP projection, 5,9 the lateral exit of virtual cutting plane was placed immediately distal to the fibular tip inside the safe zone. [5][6][7][8][10][11][12][13][14] The starting point of the medial surface was distal to the tibial tubercle considering the Tomofix ® hole D, and the virtual line was parallel to the tibial slope in the sagittal plane to prevent a change in tibial slope 2 (Figure 1). To ensure the width of lateral cortical hinge not less than 10 mm, a round cylinder measuring 30 mm in diameter and 10 mm in height (10-mm cylinder) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the standard AP projection, 5,9 the lateral exit of virtual cutting plane was placed immediately distal to the fibular tip inside the safe zone. [5][6][7][8][10][11][12][13][14] The starting point of the medial surface was distal to the tibial tubercle considering the Tomofix ® hole D, and the virtual line was parallel to the tibial slope in the sagittal plane to prevent a change in tibial slope 2 (Figure 1). To ensure the width of lateral cortical hinge not less than 10 mm, a round cylinder measuring 30 mm in diameter and 10 mm in height (10-mm cylinder) was used.…”
Section: Methodsmentioning
confidence: 99%
“…To maintain the integrity of lateral cortical hinge from opening osteotomy to completion of gap healing while preventing loss of wedge-distracted correction, most surgeons intend to localize a cutting plane of osteotomy inside the safe zone within the proximal one-third of the fibular head in the anteroposterior (AP) projection of image intensifier. [5][6][7][8] To maintain a safe zone for wedge-distracted correction, the position and direction of anterior and posterior cortical hinge points are crucial for the success of MOWHTO, at least in principle. The anterior and posterior endpoints of osteotomy and cutting plane should be intraoperatively verified by the correct intensifier view and the width of lateral cortical hinge should be adequate to prevent intraoperative lateral hinge fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The surface at the level of osteotomy is smaller on the femoral side. There is no natural "hinge-preserver" such as the fibers of the proximal tibio-fibular joint in the area of the safe zone [24,25], and the lever arm of the DFO is longer. As a result, DFO is inherently more unstable.…”
Section: State-of-the-art Treatment/ Biomechanical Problems: Hto and Dfomentioning
confidence: 99%
“… 13 However, it is associated with a major risk of intraoperative lateral hinge fracture (LHF). 7 , 9 , 12 , 27 , 35 , 38 , 40 The reported incidence of LHF after MOWHTO ranges from 0.3% to 35%. 1 , 8 , 22 , 25 , 31 , 36 , 38 , 39 Previous studies have reported that LHF is a major cause of instability, leading to serious complications such as malunion and nonunion.…”
mentioning
confidence: 99%